Ethnomathematics Study: Mathematical Ideas in Malay Weaving Motifs in Pekanbaru City as A Basis for Developing Contextual Learning - Hafilah, Putri; Dasari, Dadan; Juandi, Dadang (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
Ethnomathematics is present as contextual learning that presents mathematical aspects of culture. Culture and mathematics are integrated into aspects of people's lives everywhere, including the Riau Malay ethnic community. One of the traditional arts of the Riau Malay community is songket weaving. Each region has its characteristic motifs. This study aims to explore the mathematical aspects contained in the Riau Malay songket woven motifs in the city of Pekanbaru. The data collection technique used ethnographic principles, namely: (1) interviews; (2) participant observation; (3) documentation; and (4) field notes. The subject of this research is the social situation of the Riau community in Pekanbaru City where there is a place, focusing on the production activities of the Malay Riau songket weaving motif. The findings of this study are that weaving activities have a mathematical aspect, namely the concept of flat plane geometry. This research is expected to contribute to the development of learning that uses local cultural ideas for mathematics learning in schools, especially schools in Riau.